1997
DOI: 10.1037/0022-0663.89.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Flashcards revisited: Training poor readers to read words faster improves their comprehension of text.

Abstract: Forty-two below-average readers, between 7 and 10 years of age, were given single-word training, phrase training, or no training. Trained children learned to decode target words quickly and accurately, using flashcards; untrained children only discussed the target words and read them once. Trained and untrained children read aloud passages containing target words and were tested on their comprehension. Trained children had better comprehension than did the untrained children when questioned about passages and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 47 publications
4
83
0
4
Order By: Relevance
“…Research has been published in which transfer effects of training words in isolation to reading in context were not automatic at all (e.g., Fleisher, Jenkins, & Pany, 1979-1980Levy, Abello, & Lysynchuk, 1997). However, Tan and Nicholson (1997) found that poor readers significantly benefit from single-word training by demonstrating better comprehension of passages containing these trained words than untrained children. Maybe, these incongruous findings are related to the level of severity of the reading deficit.…”
Section: Discussionmentioning
confidence: 88%
“…Research has been published in which transfer effects of training words in isolation to reading in context were not automatic at all (e.g., Fleisher, Jenkins, & Pany, 1979-1980Levy, Abello, & Lysynchuk, 1997). However, Tan and Nicholson (1997) found that poor readers significantly benefit from single-word training by demonstrating better comprehension of passages containing these trained words than untrained children. Maybe, these incongruous findings are related to the level of severity of the reading deficit.…”
Section: Discussionmentioning
confidence: 88%
“…The comparative merits of teaching fluency versus discussion of word meanings were tested with struggling primary-school readers; it was found students who had learned to recognize the words to the point of automaticity answered more comprehension questions than students who merely were instructed on individual word meanings (Tan and Nicholson 1997). This is why fluency is now considered a prerequisite for comprehension (Snow et al 1998;Pikulski and Chard 2005 (Goswami 1999).…”
Section: Chaptermentioning
confidence: 99%
“…A reversal design would show the effectiveness of the intervention strategy and show a clear correlation between the participants' intervention scores and the implementation of the strategy. DI flashcards have been showed to be effective in various settings and content areas, but little research has been conducted on the effectiveness of increasing the accuracy of spelling (Hayter, Scott, McLaughlin, & Weber, 2007;Tan & Nicholson, 1997). If a study was replicated the strategy, it would be recommended to study the effects on a larger group of participants.…”
Section: Resultsmentioning
confidence: 99%
“…A successful method for teaching academic skills to children with special needs has the use of direct instruction (DI) flashcards (Hayter, Scott, McLaughlin, & Weber, 2007;Tan & Nicholson, 1997). Typically, DI flashcards are employed to teach and improve the fluency of various academic skills such as sight words (Higgins, McLaughlin, Derby, & Long, 2012;Hopewell, McLaughlin, & Derby, 2011;Ruwe, McLaughlin, Derby, & Johnson, 2011) basic math facts (Brasch, Williams, & McLaughlin, 2008;Erbey, McLaughlin, Derby, & Everson, 2011;Lund, McLaughlin, Neyman, & Everson, 2012;Walker, McLaughlin, & Weber, 2012), colors or shapes, (K. Herberg, McLaughlin, Derby, & Gilbert, 2011) or letter sounds (Travis, McLaughlin, Derby, Dolliver, & Carosella, 2011), and spelling (Skarr, McLaughlin, Derby, Meade, & Williams, 2012).…”
mentioning
confidence: 99%